SuperPolymyxin™ Medium for the Screening of Colistin-Resistant Gram-Negative Bacteria in Stool Samples - Przybysz, Sara M.; Correa-Martinez, Carlos; Köck, Robin; Becker, Karsten; Schaumburg, Frieder (Frontiers in Microbiology, 2018)
Colistin is one of the last resort antimicrobials for the treatment of infections caused by multidrug-resistant Gram-negative bacteria. After the emergence of transferable colistin resistance genes (mcr-1–5), a reliable culture-based screening method to detect colonization with colistin-resistant Gram-negative bacteria (CRGN) is needed. The objective of this study was to test the performance of SuperPolymyxin™ medium to screen for CRGN in stool samples and to compare different methods for the confirmation of colistin resistance (e.g. Etest®, broth microdilution [BMD], and the Rapid Polymyxin™ NP test). Colonization with CRGN was analyzed in a prospective cohort study among travelers. Stool samples (Fecal TranswabTM) taken before, during and after travel were cultured on SuperPolymyxin™ agar. Every phenotypically different colony was subcultured for species identification using MALDI-TOF mass spectrometry. Susceptibility to colistin was tested using Etest® and confirmed by BMD and the Rapid Polymyxin™ NP test. In total, 128 participants provided 1495 stool samples. After culture on SuperPolymyxin™ medium (37°C, 24–48 h), 1851 phenotypically different colonies were isolated. Isolates belonging to intrinsically colistin resistant genera (e.g. Morganella, Providencia, Proteus) or Stenotrophomonas maltophilia were excluded from further analysis (n=421). Among the remaining 1430 isolates, colistin resistance was confirmed in 279 by Etest® (19.5%) and 218 by BMD (15.3%). The Rapid Polymyxin™ NP test was compared with BMD (reference) to detect colistin resistance (specificity: 88.6%, sensitivity 71.1%). SuperPolymyxin™ medium is suitable to screen for fecal colonization with CRGN. The high proportion of colistin-susceptible isolates growing on SuperPolymyxin™ medium caused a high workload. The confirmation of CRGN with the Rapid Polymyxin™ NP Test could be a less labor-intensive alternative to BMD.